Behaviour of Cows with Johne’s Disease (Paratuberculosis) - Gemma L. Charlton; Jeanette Churches; Emma C. L. Bleach; Vivi M. Thorup (Ruminants)
Johne’s disease (JD) significantly reduces the welfare of cattle worldwide. As changes in lying and feeding behaviours are considered important tools for assessing health and early detection of diseases, the aim of this study was to compare lying and feeding behaviours of JD-positive (JD5) and JD-negative (JD0) cows around peak lactation. The cows were fitted with an accelerometer-based sensor to record step counts and lying behaviour. They were also fitted with a pressure-based halter from approximately 56 d post-partum to collect feeding and rumination data. Every 3 months, the cows were milk sampled to test for naturally occurring JD using an ELISA. JD5 cows [n = 14 (two positive results in any four consecutive ELISAs)] were matched to JD0 cows [n = 14 (consecutive negative ELISAs)] based on lactation stage, parity, age, and milk yield. Of the 28 cows, 9 JD5 and 9 JD0 cows provided sensor data for analysis. JD5 cows spent 1.7 h/d less lying compared to JD0 cows. No differences in time spent eating were found; however, JD5 cows spent 1.1 h/d longer ruminating and produced 80 more feed boluses/d than JD0 cows around week 8 of lactation. The reason JD5 and JD0 cows behave differently around peak lactation is unclear and therefore warrants further investigation focusing on behaviour, milk yield, and feed intake among cows with JD.